2016
DOI: 10.1186/s13046-016-0298-y
|View full text |Cite
|
Sign up to set email alerts
|

HIF-2α promotes epithelial-mesenchymal transition through regulating Twist2 binding to the promoter of E-cadherin in pancreatic cancer

Abstract: BackgroundEpithelial-mesenchymal transition (EMT) is a dedifferentiation process that mainly involves in mesenchymal marker upregulation, epithelial maker downregulation and cell polarity loss. Related hypoxia factors play a crucial role in EMT, however, it remains few evidence to clarify the role of HIF-2α in EMT in pancreatic cancer.MethodIn this study, we investigated the expression of HIF-2α and E-cadherin by immunohistochemistry in 70 pancreatic cancer patients, as well as the correlation to the clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 31 publications
2
50
0
1
Order By: Relevance
“…A correlation between hypoxia and pancreatic cancer has been recognized for a number of years (21), and a role for HIF-1a and HIF-2a in pancreatic cancer has previously been investigated (22,23). In this study, we showed that HIF-3a expression is stimulated to a greater extent than either HIF-1a or HIF-2a under hypoxic conditions in pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 57%
“…A correlation between hypoxia and pancreatic cancer has been recognized for a number of years (21), and a role for HIF-1a and HIF-2a in pancreatic cancer has previously been investigated (22,23). In this study, we showed that HIF-3a expression is stimulated to a greater extent than either HIF-1a or HIF-2a under hypoxic conditions in pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 57%
“…Epithelial-to-mesenchymal transition (EMT) is a process through which epithelial cells acquire motile and invasive properties and change into mesenchymal-like cells [8,9]. Naturally, EMT occurs in cell development, but during carcinogenesis, it can augment oncogenic transformation of cancer cells, making them prone to migration and invasion [8].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the other isoforms of HIF [79], clinically HIF-1α appears to be important in PDAC survival. Using immunohistochemical methods, Sun et al demonstrated that HIF-1α in PDAC specimens has a strong association with prognosis and correlates with expression of vascular endothelial growth factor (VEGF) [2].…”
Section: Discussionmentioning
confidence: 99%
“…The cellular response to hypoxia is primarily mediated by hypoxia-inducible transcription factors (HIF-1, 2, and 3), of which the HIF-1 isoform is well established to correlate with pancreatic cancer (PDAC) metastasis and prognosis [16] while the relationship with the other isoforms is inconclusive [79]. HIF-1 is active in its heterodimeric form, made up of HIF-1α and HIF-1β subunits.…”
Section: Introductionmentioning
confidence: 99%